A mixing model for comprehensive evaluation on the removal performance of portable air cleaners. Issue 1 (September 2020) - Yang, Rancun; Yin, Keke; Xu, Peng; Wu, Peipei
Abstract: A mixing model based on the indoor air quality obtained from statistics was developed to evaluate the comprehensive removal performance of Portable air cleaners (PACs), which have been inadequate in current research. PM0.3-2.5, formaldehyde, acetaldehyde, acetone, toluene, n-butyl acetate, ethylbenzene, xylene, styrene, and n-undecane were selected as the typical components, and initial concentrations and emission procedure were optimized. The relative standard deviations of repeatability tests were under 10%, which make the model exhibit fairly good reproducibility, stability and reusability, and are considered suitable for the estimation of the comprehensive removal performance of PACs.